On independence of characteristics of asymptotic behavior of entire functions - Azarin, V. S. (Математическая физика, анализ, геометрия, 2002)
It is known [6, Ch. 3, Theorem 18] that using any total family of asymptotic characteristics, we have a possibility to learn whether an entire function of finite order is a function of completely regular growth. However, the main result of this paper shows that all these characteristics do not give a possibility to know whether a function has an H-multiplicator [4].